PEMANFAATAN KOMIK BERBASIS BRAIN BASED LEARNING SEBAGAI SUMBER BELAJAR MANDIRI PADA MATERI HUKUM KEPLER UNTUK MENINGKATKAN PEMAHAMAN KONSEP - Dalilah, Kania; Rusnayati, Heni; Kaniawati, Ida (Journal of Teaching and Learning Physics, 2023)
This research was carried out in the form of comic design using the Brain Based Learning approach as a Kepler's Law learning material, which was used as a source of independent learning. The research goal is to determine the feasibility of using comics to help students understand the material that was removed during online learning. The research and development (R&D) methods were used, and the comic design was based on the ADDIE model framework. The Cloze test, pretest-posttest, and student response questionnaires were also used as assessment instruments in this research. The Cloze test is given to measure the readability of comics by students. Results were then analyzed through a quantitative descriptive approach. A pre-posttest instrument was used to measure the increase in concept understanding through the use of N-gain. Student response questionnaires were used to assess feedback from students regarding the use of comics as a source of independent learning. The research was conducted in one senior high school in Bandung City, with instruments then distributed to 38 students in 10th grade. Results of the cloze test analysis showed that the comics could be used independently by students, verified with a score of 91.33%. Results of the pretest-posttest showed an N-gain value of 0.5, which indicates an increase in student's conceptual understanding at a moderate level. The results of the student response questionnaire filled out by 24 respondents showed a positive comics response with a score of 76.26%. Thus, it is determined that comics designed using a Brain Based Learning approach are feasible and able to increase students' understanding of concepts.